Binational Cooperation and Twinning: A View from the US–Mexican Border, San Diego, California, and Tijuana, Baja California. Issue 4 (2nd October 2017) - Ganster, Paul; Collins, Kimberly
ABSTRACT: Institutionalization of binational cooperation is an important precondition for twinning to develop in border cities. Through a historical review of the San Diego–Tijuana region's growth and binational cooperation, this paper explores possible areas of twinning. Generally, the cities and municipalities along the US–Mexican border have not experienced twinning, unlike their counterparts in some parts of Europe. Systems of legal federalism in combination with the US and Mexican federal governments' lack of will to support local transborder collaboration help explain the absence of twinning in the San Diego–Tijuana region. This article concludes that in the era of globalization and regional development, it is important for local governments to be able to fully enter into twinning arrangements to take advantage of opportunities and address challenges inherent in the binational regional context.